Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2019)
A dataset containing 18916274 species occurrences available in GBIF matching the query: (Query is too complex. Can be viewed on the landing page) The dataset includes 18916274 records from 3479 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0021780-191105090559680/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences